Bite the bullet ; Jon of Arts ; Silent war [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Tackles oil price increase, the Oil Price Stabilization fund established to support world fluctuation ; interview with Jon Santos being a new comedian, famous for impersonations ; and with Victor Corpus, a PMA instructor who joined the NPA, about his return to the Arm Forces of the Philippines.
Bite the bullet (14 min.) -- Jon of Art (17 min.) -- Victor Corpus (13 min.)
VHS.
Keywords: Corpus, Victor; Santos, Jon; Petroleum products -- Prices; Fictitious names -- Philippines; Petroleum industry and trade -- Philippines